Ternary bulk heterojunction for wide spectral range organic photodetectors - Shin, Hojung; Kim, Jaehoon; Lee, Changhee (Journal of the Korean Physical Society, 2017)
Ternary bulk heterojunction (BHJ) system, dual electron donors and an acceptor, was studied for developing wide spectral range organic photodetectors (OPDs). With two electron donor polymers with different bandgaps and an efficient electron acceptor of [6,6]-Phenyl-C71-butyric acid methyl ester (PC 70 BM), different blend ratios for ternary BHJ OPD were examined to achieve high photoresponsivity over a wide spectral range. OPDs based on ternary BHJ showed improved photovoltage response compared to binary BHJ. Current-voltage (J-V) characteristics as a function of external bias and light illumination were measured to reveal the underlying charge recombination mechanism which is found to be dominantly ruled by space charge limit (SCL) effect. Additional in-depth analyses including absorbance, cross-section scanning electron microscope (SEM), incident photon-to-electron conversion efficiency (IPCE) were performed.